The Role of Tape Mayang Madu MSME in Enhancing Rural Community Welfare from an Islamic Economic Perspective - Ramadani Farid (STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
Rural micro, small, and medium enterprises are important drivers of community welfare because they create employment, increase household income, and connect local agricultural resources with wider markets. This study aims to analyze the role of Tape Mayang Madu MSME in improving the economy of the community in Tegalwaru Village, Mayang District, Jember, from the perspective of Islamic economics. The study employed a qualitative descriptive approach, using field-based data collected through interviews with the MSME owner, workers, cassava farmers, resellers, and surrounding community members. The data were interpreted to identify how the enterprise contributes to income improvement, labor absorption, agricultural linkage, land utilization, and unemployment reduction. The findings show that Tape Mayang Madu MSME contributes to community economic improvement through several mechanisms. It employs 15 local workers, provides temporary piece-rate work during high-demand periods, involves 11 active resellers from several regions, purchases cassava from local farmers, and rents agricultural land owned by village residents. These practices create direct and indirect income opportunities for workers, farmers, landowners, and distributors. The enterprise also helps reduce unemployment by offering accessible jobs for residents with limited educational backgrounds. From an Islamic economic perspective, its practices reflect mutual benefit, productive resource use, fairness, and community welfare. The study concludes that Tape Mayang Madu MSME functions as a locally embedded economic institution that supports rural welfare and provides a practical model for community-based MSME development.